Exportaciones de rosas y su incidencia en el sector florícola - Cun Apolinario, Yadira Gabriela (2022)
Exports provide growth and sustainability to economies; developing countriescommonly export raw materials and low-industrialized products, limiting their progress.Ecuador sustains its economy in oil activity and agricultural production, where roses arethe most important product of the floricultural sector and distinctive export quality. The research studied rose exports and their incidences in the floricultural sector in the period2016- 2020, through exchanges with the United States in a context affected by the Covid-19 pandemic. Descriptive documentary analytical research was carried out in a sample defined by two units of study: export of roses and floriculture sector, applying documentary observation and critical analysis to collect secondary information, interpreted qualitatively and quantitatively. The most productive cultivation techniques and the behavior of exports were analyzed, leading to determine their impact on floriculture and generate strategies for the resurgence of the international market. It was concluded that in the specific case of the United States, the United States is not the only one to do so. In the US in the period 2016-2020, exports of roses do not have a direct proportional impact on the total results of the flower sector.